2016
DOI: 10.1097/md.0000000000003213
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Chinese Patients With Giant Cell Arteritis (GCA)

Abstract: A retrospective study was performed on 70 giant cell arteritis (GCA) patients in Peking Union Medical College Hospital (PUMCH). The aim of this study was to describe the clinical features of these Chinese GCA patients and explore the possible associated factors for severe ischemic manifestations. Medical charts of all patients were reviewed, and the demographic, clinical, and laboratory data were analyzed. The mean age at disease onset was 65.2 years old, and the ratio of male to female was 1:1. Fever and head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The epidemiological studies have rarely been addressed and according to Kobayashi et al, the prevalence in Japan is 1.47 per 100 000 [ 4 ]. Two large sample studies in China mainland showed the clinical manifestations of GCA in Chinese patients were similar to those previously described in literature [ 5 , 6 ]. Arteritic anterior ischemic optic neuropathy (A-AION) due to GCA, which accounting for 85% of cases of permanent vision loss [ 7 ], had not been reported in China so far, except for several presumed cases without biopsy published in non-English literature.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The epidemiological studies have rarely been addressed and according to Kobayashi et al, the prevalence in Japan is 1.47 per 100 000 [ 4 ]. Two large sample studies in China mainland showed the clinical manifestations of GCA in Chinese patients were similar to those previously described in literature [ 5 , 6 ]. Arteritic anterior ischemic optic neuropathy (A-AION) due to GCA, which accounting for 85% of cases of permanent vision loss [ 7 ], had not been reported in China so far, except for several presumed cases without biopsy published in non-English literature.…”
Section: Introductionsupporting
confidence: 82%
“…GCA represents a rare systematic granulomatous vasculitis in Asian, with fever and headache as the most prominent symptoms at onset [ 5 , 6 ]. An arteritic anterior ischemic optic neuropathy (A-AION) from inflammatory occlusion of posterior ciliary artery is the most common cause of permanent visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking may represent a cofactor, aiding rather than triggering GCA development [6] by impairing arterial endothelium and oestrogen synthesis [7]. Smoking has also been associated with more severe ischaemic symptoms [8].…”
Section: Reviewmentioning
confidence: 99%
“…Among these, cranial symptoms and fever are the most common. [ 2 ] Polymyalgia rheumatica and GCA represent either different manifestations of the same disease or overlapping conditions. Approximately 40% to 60% patients diagnosed with GCA also have polymyalgia rheumatica, [ 3 ] which is characterized by myalgia and arthralgia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The most severe complications of GCA are ischemic manifestations, such as permanent visual loss and stroke, which constitute 15%-30% of GCA cases [ 4 ] and leads to chronic disabilities among GCA patients. [ 2 ] For these patients, early initiation of high-dose GC therapy results in prompt remission of symptoms. [ 1 ] However, some patients show GC-resistant potential, that is, they have inadequate response to standard GC for induction of remission.…”
Section: Introductionmentioning
confidence: 99%